1889 N.C. Sess. Laws 820, ch. 178, § 3. - (:unkn) unknown (General Publisher, 1889)
That it shall be a misdemeanor for any person to . . . fire off a gun or pistol in hearing distance of those assembled for or occupied in divine worship at said church.
--
Keywords: DISCHARGE